2019
DOI: 10.1111/jbg.12420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selection and selective genotyping for creation of reference on bias and accuracy of genomic prediction

Abstract: Reference populations for genomic selection usually involve selected individuals, which may result in biased prediction of estimated genomic breeding values (GEBV). In a simulation study, bias and accuracy of GEBV were explored for various genetic models with individuals selectively genotyped in a typical nucleus breeding program. We compared the performance of three existing methods, that is, Best Linear Unbiased Prediction of breeding values using pedigree-based relationships (PBLUP), genomic relationships f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 46 publications
7
22
0
Order By: Relevance
“…In many breeding programs, genotyping is limited to phenotypically superior animals, referred to as selective genotyping of top animals. Such selective genotyping leads to biased predictions of genomic breeding values (GEBV) when genomic-based best linear unbiased prediction (GBLUP) is used (Gowane et al, 2019;Wang et al, 2020). For example, Wang et al (2020) showed that the use of a combined matrix (Christensen and Lund, 2010;Aguilar et al, 2011) of pedigree and genomic relationships in a single-step GBLUP (ssGBLUP) prediction resulted in the upward bias of GEBV and overestimation of variance components when only a proportion of top individuals were genotyped.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In many breeding programs, genotyping is limited to phenotypically superior animals, referred to as selective genotyping of top animals. Such selective genotyping leads to biased predictions of genomic breeding values (GEBV) when genomic-based best linear unbiased prediction (GBLUP) is used (Gowane et al, 2019;Wang et al, 2020). For example, Wang et al (2020) showed that the use of a combined matrix (Christensen and Lund, 2010;Aguilar et al, 2011) of pedigree and genomic relationships in a single-step GBLUP (ssGBLUP) prediction resulted in the upward bias of GEBV and overestimation of variance components when only a proportion of top individuals were genotyped.…”
Section: Introductionmentioning
confidence: 99%
“…Gowane et al (2019) also showed that with selective genotyping of top animals, the use of a genomic relationship matrix in a GBLUP prediction led to biased GEBV, but the use of a combined relationship matrix (Christensen and Lund, 2010;Aguilar et al, 2011) constructed from pedigree and genomic information resulted in the unbiased prediction of GEBV. Compared to random genotyping or selective genotyping of phenotypically contrasting animals, selective genotyping of top animals in a reference population for training genomic selection models less accurately predicted GEBV (Boligon et al, 2012;Gowane et al, 2019). According to Gowane et al (2019), genotyping of phenotypically contrasting animals (selective genotyping of top and bottom animals) for selection candidates is superior to selective genotyping of top animals.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations